2022
DOI: 10.3389/fpsyg.2022.924302
|View full text |Cite
|
Sign up to set email alerts
|

From Employment Pressure to Entrepreneurial Motivation: An Empirical Analysis of College Students in 14 Universities in China

Abstract: Entrepreneurship is vital in solving the challenges involved in the employment of college students in China. The two viewpoints on the relationship between employment and entrepreneurship are the refugee effect and the entrepreneurial effect. However, the micro-mechanism of this association is yet to be comprehensively discussed. Based on the refugee effect and entrepreneurial effect, along with the entrepreneurial values as the mediating mechanism and the entrepreneurial environment as the moderating variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Statistics from China's Ministry of Education of the People's Republic of China (n.d.) showed that the number of college students in China was 30.32 million in 2019, and as of 2022 had risen as high as 36.56 million, with rural college students accounting for about 47% of the total. The above data is evidence of the high growth rate in the number of college students in China in recent years, and the number of employed people is also increasing (Senekal and Smith, 2022;Yin, 2022). However, there is no large-scale postgraduate expansion and recruitment program in China, which leads to a grim employment situation for college students (Pei, 2021;Li, 2022;Xiong et al, 2022;Zhi, 2023).…”
Section: Introductionmentioning
confidence: 89%
“…Statistics from China's Ministry of Education of the People's Republic of China (n.d.) showed that the number of college students in China was 30.32 million in 2019, and as of 2022 had risen as high as 36.56 million, with rural college students accounting for about 47% of the total. The above data is evidence of the high growth rate in the number of college students in China in recent years, and the number of employed people is also increasing (Senekal and Smith, 2022;Yin, 2022). However, there is no large-scale postgraduate expansion and recruitment program in China, which leads to a grim employment situation for college students (Pei, 2021;Li, 2022;Xiong et al, 2022;Zhi, 2023).…”
Section: Introductionmentioning
confidence: 89%
“…However, their expected goal is not achieved-they do not find satisfactory jobs, but are not willing to stay where they are. Therefore, under the function of self-regulation, they choose to start a business to meet the survival needs of themselves or their families (Yin 2022). Entrepreneurs driven by opportunity motivation see business opportunities and are full of confidence in entrepreneurship.…”
Section: Entrepreneurial Risk Perception and Entrepreneurial Motivationmentioning
confidence: 99%
“…Leisure purpose means the aim to alleviate the stress of life and get a pleasant experience (Kleiber, Hutchinson, & Williams, 2002). As mentioned before, most younger adults face the dual pressures of study and work, resulting in mental anxiety and depression (Yin, 2022). According to the relevant statistics stated by Yin (2022), nearly 900,000 younger graduates have not found suitable jobs in 2020.…”
Section: Effect Of Influencing Factorsmentioning
confidence: 99%
“…As mentioned before, most younger adults face the dual pressures of study and work, resulting in mental anxiety and depression (Yin, 2022). According to the relevant statistics stated by Yin (2022), nearly 900,000 younger graduates have not found suitable jobs in 2020. Intangible employment stress significantly harms their mental health.…”
Section: Effect Of Influencing Factorsmentioning
confidence: 99%